Little mouse - Murray, Alison, (Illustrator) (New York, N.Y. : Disney.Hyperion Books, 2013)
A little girl explains how she does not always fit her nickname, little mouse, but it is perfect for when she is cuddling with her mother.
Keywords: Nicknames -- Fiction; Mother and child -- Fiction